Prevalence of and factors contributing to glue sniffing in the South Asian Association for Regional Cooperation (SAARC) region: a scoping review and meta-analysis - Munawar, Khadeeja; Choudhry, Riaz Fahad; Abdul Hadi, Muhammad; Khan, Tahir Mehmood (Taylor & Francis, 2020)
Background: Although glue sniffing has been linked with significant morbidity and mortality, it is still under-researched and poorly recognized issue globally. Objective: A scoping review was performed to identify the factors and outcomes related to glue sniffing in India, Pakistan, Nepal and Bangladesh. Methods: Ten databases; Medline via Ovid, Google scholar, EBSCOhost (CINAHL Plus), ProQuest Central, PsycInfo, IndMED, Ovid Embase, Scopus, PubMed, and Science Direct were searched from their inception to January 2019 for both qualitative and quantitative studies examining any aspect of glue-sniffing. Studies published only in English language were included. Prevalence of glue-sniffing in SAARC region was the primary outcome measure. Findings: Of 8951studies screened, 344 were assessed for eligibility and 31 studies were included. The majority of the studies were conducted in India (15) and Pakistan (11). Meta-analysis of proportion, using random effects model, for both primary and secondary outcomes found that the highest incidence of glue sniffing was 57% (0.57, CI 95% 0.49–0.66) in India. The overall incidence of tobacco and naswar (snuff) as was 83% (0.83, 95% CI 0.80–0.86). Conclusions: The prevalence of glue sniffing, especially among street children, is alarmingly high and presents a challenge for health and social services for countries in SAARC region. More research work is required to examine long term impact of glue sniffing on physical and mental health.